Dyslipidemia Patterns among Type 2 Diabetes Patients: Evidence from a Hospital Based Study in Faridabad, Haryana - Umesh Kumar Sharma; Anuradha Jayaraman (The Bioscan, 2024)
Dyslipidemia is a common metabolic abnormality in patients with type 2 diabetes mellitus (T2DM) and a major contributor to cardiovascular risk. This cross-sectional study, conducted at a multispecialty hospital in Faridabad, Haryana, evaluated 947 patients with T2DM from urban and rural populations to determine the prevalence and patterns of dyslipidemia. Results revealed a higher burden of dyslipidemia in urban patients, with low HDL-C, high LDL-C, and elevated triglycerides being the most frequent abnormalities. Gender differences showed men with higher triglycerides and women with relatively higher HDL-C. The findings highlight the need for early screening, lifestyle modification, and targeted interventions to reduce cardiovascular complications in T2DM.